Advanced Techniques for Knowledge Engineering and Innovative Applications 16th International Conference, KES 2012, San Sebastian, Spain, September 10-12, 2012, Revised Selected Papers - Tweedale, Jeffrey W.; Jain, Lakhmi C.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed proceedings of the 16th International Conference on Knowledge-Based Intelligent Information and Engineering Systems, KES 2012, held in San Sebastian, Spain, in September 2012. The 21 revised papers were carefully reviewed and selected from 254 submissions. Topics of interest include the exploitation of AI techniques, most recent research in information technologies and dynamic ontologies.
Exploitation of AI techniques -- Most recent research -- Information technologies -- Dynamic ontologies.
Keywords: Computer science; Information systems; Data mining; Artificial intelligence; Computer vision; Computer Science; Artificial Intelligence (incl. Robotics).; Data Mining and Knowledge Discovery; Computer Imaging, Vision, Pattern Recognition and Graphics; Information Systems and Communication Service